Premalignant and Malignant Skin Lesions in Two Recipients of Vascularized Composite Tissue Allografts (Face, Hands) - Jean Kanitakis; Palmina Petruzzo; Aram Gazarian; Sylvie Testelin; Bernard Devauchelle; Lionel Badet; Jean-Michel Dubernard; Emmanuel Morelon (Case Reports in Transplantation)
Recipients of solid organ transplants (RSOT) have a highly increased risk for developing cutaneous premalignant and malignant lesions, favored by the lifelong immunosuppression. Vascularized composite tissue allografts (VCA) have been introduced recently, and relevant data are sparse. Two patients with skin cancers (one with basal cell carcinoma and one with squamous cell carcinomas) have been so far reported in this patient group. Since 2000 we have been following 9 recipients of VCA (3 face, 6 bilateral hands) for the development of rejection and complications of the immunosuppressive treatment. Among the 9 patients, one face-grafted recipient was diagnosed with nodular-pigmented basal cell carcinoma of her own facial skin 6 years after graft, and one patient with double hand allografts developed disseminated superficial actinic porokeratosis, a potentially premalignant dermatosis, on her skin of the arm and legs. Similar to RSOT, recipients of VCA are prone to develop cutaneous premalignant and malignant lesions. Prevention should be applied through sun-protective measures, regular skin examination, and early treatment of premalignant lesions.